Chapter 11 - Sequestration of carbon dioxide into petroleum reservoir for enhanced oil and gas recovery - Uddin Monir, Minhaj; Azrina, Abd Aziz; Khatun, Fatema; Tarek, Mostafa; N. Vo, Dai-Viet (Elsevier, 2022)
This chapter presents a detailed and important study of the effectiveness of enhanced oil/gas technology in an unconventional petroleum reservoir. To meet the challenges of ever-increasing amount of greenhouse gas emissions and the long-term need for energy supplies, enhanced oil/gas recovery (EOR/EGR) techniques, which are the most appropriate approach to be used for both scientific and industrial benefits, are systematically explored. Owing to the decline of fossil energy, the global demand for energy could not be fulfilled by oil and natural gas. Generally, EOR/EGR is used to maintain critically regulated pore strength where gases (e.g., CO2, CO, N2, etc.) are injected into the petroleum reservoir through a vertical well. These techniques for oil recovery are more efficient, while primary and secondary techniques for oil recovery are inconvenient. The use of CO2 storage or EOR/EGR in oil or gas reserves is more complicated due to their significant variations in porosity and permeability. This chapter concludes with an important debate on the prospects and problems of CO2 sequestration in oil and gas reservoirs for EOR/EGR and future avenues for study.